2009
DOI: 10.1099/mic.0.029819-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biochemical identification of the chorismate mutase from Corynebacterium glutamicum

Abstract: Chorismate mutase (CM) catalyses the rearrangement of chorismate to prephenate and is also the first and the key enzyme that diverges the shikimate pathway to either tryptophan (Trp) or phenylalanine (Phe) and tyrosine (Tyr). Corynebacterium glutamicum is one of the most important amino acid producers for the fermentation industry and has been widely investigated. However, the gene(s) encoding CM has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(51 reference statements)
1
7
1
Order By: Relevance
“…However, it was still possible to accurately determine the ratio k cat / K m for isolated native CgCM as 110 M –1 s –1 (Table ). This value is of the same order of magnitude as the k cat / K m previously measured for N-terminally His-tagged variants of CgCM (370 and 390 ± 60 M –1 s –1 ) , and 3–4 orders of magnitude below that of typical DS-independent CMs. Upon addition of CgDS, the level of CgCM catalysis can be boosted 180-fold, proving a dramatic activation effect similar to that observed for the M. tuberculosis system (Table ). This is in stark contrast to the data of the CgCM–CgDS study published recently, where no stimulation of CM activity was observed …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, it was still possible to accurately determine the ratio k cat / K m for isolated native CgCM as 110 M –1 s –1 (Table ). This value is of the same order of magnitude as the k cat / K m previously measured for N-terminally His-tagged variants of CgCM (370 and 390 ± 60 M –1 s –1 ) , and 3–4 orders of magnitude below that of typical DS-independent CMs. Upon addition of CgDS, the level of CgCM catalysis can be boosted 180-fold, proving a dramatic activation effect similar to that observed for the M. tuberculosis system (Table ). This is in stark contrast to the data of the CgCM–CgDS study published recently, where no stimulation of CM activity was observed …”
Section: Resultssupporting
confidence: 74%
“…It has also been shown that MtDS can heterologously increase the activity of CgCM, which suggested that CM–DS complex formation plays a similar role in C. glutamicum and M. tuberculosis . When the C. glutamicum enzymes were first studied (before Brevibacterium flavum was reclassified as C. glutamicum ), it was not possible to detect any CM activity in the absence of DS, pointing to a dramatic activating effect upon complex formation. , However, recent publications stated that CgDS did not enhance the catalytic activity of CgCM. , Thus, there is currently contradictory information in the literature regarding the regulation at one of the key branch points in the metabolism of this biotechnologically important bacterium.…”
mentioning
confidence: 99%
“…To improve conversion of shikimate to anthranilate from about half to full conversion (compare about 1.4 g·L −1 of shikimate and 2.6 g·L −1 anthranilate produced by NMA105 in bioreactor cultivation; Figure 6 ), expression of the operon aroC KB encoding chorismate synthase, shikimate kinase, and 3-dehydroquinate synthase may be boosted, e.g., by changing the endogenous promoter for the strong promoter P tuf and using shikimate kinase from Methanocaldococcus jannaschii as shown previously [ 36 ]. In addition, various studies have shown that deletion of the chorismate mutase will increase the carbon flux towards tryptophan biosynthesis [ 36 , 40 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, the three DAHP synthase isoenzymes AroF, AroG and AroH encoded by three paralogous genes aroF, aroG and aroH, respectively, share high sequence similarities (Jossek et al, 2001) and are feedback inhibited by L-tyrosine (L-Tyr), L-phenylalanine (L-Phe) and L-tryptophan (L-Trp), respectively (Brown & Somerville, 1971;Shultz et al, 1984;Ger et al, 1994;Pittard, 1996). In contrast, Corynebacterium glutamicum has only two DAHP synthase isoenzymes, AroF (encoded by aroF) and AroG (encoded by aroG), which are feedback inhibited by L-Tyr, and by L-Tyr, L-Phe, prephenate and chorismate, respectively (Tribe et al, 1976;Liu et al, 2008;Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Corynebacterium glutamicum , a gram‐positive model bacterium, has been widely used for producing many valuable secondary products (Takors et al ., ; Becker & Wittmann, ; Gopinath et al ., ) and proteins (Date et al ., ; Kikuchi et al ., ; Itaya et al ., ) with many advantages (Eggeling & Bott, ). In fact, C. glutamicum has also been engineered to produce l ‐Phe by overexpressing the committed enzymes DAHP synthase and PheA (Ikeda & Katsumata, ; Ikeda et al ., ; Li et al ., ) or optimizing the cultivation process (Shu & Liao, ). More recently, we significantly increased the production of l ‐Phe by co‐overexpressing the E. coli wild‐type aroH and pheA fbr (Zhang et al ., ), indicating the crucial role of the DAHP synthase.…”
Section: Introductionmentioning
confidence: 99%